Surface studies of the Fe/Mo(110) and Fe/W(100) epitaxial systems - Murphy, Shane (Trinity College (Dublin, Ireland). School of Physics, 2001)
This thesis describes the investigation of ultrathin Fe film growth on the Mo(110) and W(100) surfaces, using scanning tunneling microscopy (STM), low-energy electron diffraction (LEED) and Auger electron spectroscopy (AES). A general review of the current understanding of epitaxial film growth is given, covering both thermodynamic and kinetic aspects of theory. The experimental set-up and conditions under which the Fe/Mo(110) and Fe/W(100) epitaxial systems were studied are described. This includes a description of the preparation procedure for novel STM tips of MnNi, Fe and Cr, that were used in the study.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin